Answer:
Option A is correct, i.e. -3x² -x +3 = -3x²
Explanation:
We can rearrange the terms, and combine like terms to get each equation in standard form of quadratic equation like ax²+bx+c=0.
It must have degree 2 to be solved using quadratic formula.
Option A: -3x² -x +3 = -3x²
Rearranging the terms:-
3x² -3x² -x +3 = 0
Combining like terms:-
0 -x +3 = 0
-x +3 = 0
This is linear equation with degree 1 and can be solved without quadratic formula.
Hence, option A is correct, i.e. -3x² -x +3 = -3x²